QSAR STUDY OF ANTIOXIDANT AND VASODILATATORY ACTIVITY OF PHENOLIC ACIDS - Medic-Saric, M.; Rastija, V. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Phenolic acids are aromatic secondary plant metabolites that are widely spread throughout the plant kingdom. The recent interest in phenolic acids comes from their potential protective role against oxidative damage diseases (coronary heart disease, stroke, and cancers) [1]. In order to explain the contribution of various structure-related parameters on biological activities of nine phenolic acids, antioxidative [Ferric Reducing Antioxidant Power (FRAP/mol L-1), Trolox Equivalent Antioxidant Capacity (TEAC/mol L-1)] and vasodilatatory activities were correlated with “two-dimensional” (2D) topological indices, “three-dimensional” (3D) molecular descriptors, calculated physicochemical parameters and variable indicators of the number and position of hydroxyl groups on the phenyl ring. The best diparametric QSAR model for the prediction of FRAP was obtained with Topological Polar Surface Area (TPSA) and mean distance degree deviation (MDDD) (r2 = 0.950; F = 60.93). A statistically significant model for the prediction of TEAC values was obtained with two GETAWAY descriptors, R7p i HATS3e (r2 = 0.955; F = 64.00). The best model for vasodilatatory activity was obtained by multiple regression with TPSA and GETAWAY descriptor R+3(u) (r2 = 0.916; F = 32.76). The results of the QSAR study have shown that biological activity of phenolic acids largely depends on hydrophylicity, electronegativity, polarizability, size and the shape of molecules. References: [1] R J Robbins, 2003, J. Agric. Food Chem. 51 2866-2887